Effect of topical Areca palm L. hydroalcoholic extract on burn wound healing in rats - Abbasy, Zahra; Tameh, Abolfazl Azami; Kermani, Reza Mozaffari; Arani, Hamid Zaferani; Talaei, Sayyed Alireza (Journal of Advanced Veterinary and Animal Research, 2021)
Objectives: Wound healing is a complex and dynamic process that begins immediately following tissue injury and continues until the wound is completely healed and remodeled. Applying the most effective burn repair techniques is a constant challenge in medicine. Antiulcerogenic and wound healing properties of Areca palm leaves have been validated through various investigations and animal studies. This study aimed to determine the potential for A. palm hydroalcoholic extract to heal burn wounds in rats. Materials and Methods: For 14 days, we examined 40 male Wistar albino rats in 5 groups: those receiving 1% silver sulfadiazine cream (reference standard), those receiving eucerin (positive control), and those receiving 5% and 10% ointments of Areca catechu hydroalcoholic extract (treatment groups). No treatment was given to the negative control group. On the dorsal part of the animals’ necks, burn wounds were made. After the rats were sacrificed, the wound contraction rate (WCR) was determined, and the wound sites were histopathologically examined. Results: On the 14th day, the WCR was significantly higher in rats treated with A. palm 10% extract ointment than in rats treated with 5% extract, positive or negative control groups (p < 0.001), or rats treated with silver sulphfadiazine (p = 0.01). After applying a 10% extract ointment to burn wound sites, complete healing occurred with only mild tissue inflammation and edema. Conclusion: The study’s findings indicate that the hydroalcoholic extract of A. palm L. has the ability to expedite the wound healing process. Additional research is necessary to identify the compounds responsible for their wound healing properties and comprehend their action mechanism. J. Adv. Vet. Anim. Res., 8(4): 619–628, December 2021 http://doi.org/10.5455/javar.2021.h553